THE INFLUENCE OF AN AUDITOR'S EXPERTISE, OBEDIENCE PRESSURE, AND INDEPENDENCE ON AUDIT JUDGMENT - Tikkos Sitanggang (Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2020)
This study aims to empirically test whether the auditor’s expertise, obedience pressure, and independence affects the audit judgment. The data used is the primary data through questionnaires that contain the answers of respondents. The population in this study auditor registered in the central Jakarta public accountant. The selected sample is 80 respondents with technical purposive sampling. This research uses quantitative method where the data obtained from questionnaire. Analysis of research data using multiple linear regression, with SPSS version 24. Based on the results of the analysis that has been done, this study shows that the auditor’s expertise, obedience pressure, and independence, have a positive and significant impact on the use of audit judgment compliance with adjusted R square of 74.7%. Partially, the results of this study indicate that auditor’s expertise, obedience pressure, and independence together positively and significantly influence the audit judgment.